Semiotic Analysis of Gender Representation on Printed Advertisements in œSwedish Magazine - Savira, Salwa; Manullang, Elisa Betty (Universitas Negeri Medan, 2022)
Semiotic analysis of gender representation on printed advertisements used in œSWEDISH magazine. The objectives of this study were to identify the element and colour of symbol used in Gender representation in printed advertisement of œSwedish magazine. The study was conducting by using descriptive qualitative method. The data of the study were obtained from the Magazine in Sweden the Swedish version of Cosmopolitan Magazine Advertisement which consisted of some pictures. The data analysis were taken downloading, looking for, describing and explaining the data. The data were analyze based on the theory by Wells, Burnett, and Moriaty about element and colour of symbol in printed advertisement. The findings indicted that there were consisted of the element and colour of symbol in printed advertisement, there were the first element of symbol in advertising layout for example (figure 4.1) this advertisement was a symbolize confident characteristic with the logotypes brand the picture, advertising content for example (figure 4.3) the meaning of this advertisement was found if you wear products from Chanel you will look closed and cold because this advertisement was product centered format which was the case of fashion advertising means price information. The second colour of symbol in colour association for example (figure 4.5) the meaning of this advertisement was clear water and clear sky blue which symbolizes nature, freshness and tranquility, logotype colour for example (figure 4.7) the meaning of this advertisement the red H&M logotype or brand text that symbolizes logotypes or logos to attract brand attention, body colour for example (figure 4.9) the meaning in this advertisement white is the body colour or common object colour in advertisements that symbolizes the art in the layout of the advertisement, colour contrast for example (figure 4.11) the meaning of this advertisement it looks like it has a light background which is white, which symbolizes art in the advertisement. The finding of this study hoped for useful resource for the development of semiotic study toward commercial works.